COMMITMENT MOTHER AND BEHAVIORAL PREVENTION OF PICKY EATING ON TODDLER - Dona Muji Fitriana; Yuni Sufyanti Arief; Ilya Krisnana (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2020)
Background: Picky eating is a picky behavior that can be interpreted as a rejection of certain types of food or fear of trying new foods. Picky eating can make some problems inadequacy of nutrition and impact on child growth if it's not properly handled and left prolongObjectives: The purpose of this study was determined to describe the relationship between commitment mothers and behavioral prevention of picky eating on toddler.Methods: The research used correlational analytic study with cross-sectional design. The Independent variable in this study is mother’s commitment and the dependent variable is behavioral prevention of picky eating. The population was mothers with toddler age children in the working area at the Public Health Center of Kedawung 1, Sragen, Central Java. A sample of 120 mothers were selected by purposive sampling. Data were collected using questionnaires demographic of the respondent, mother’s commitment, and behavioral prevention of picky eating that compiled by the researcher. This questionnaire has been tested for validity and reliability, and then analyzed used Spearman-rank test.Results: The results of this study showed that the mother's commitment to picky eating prevention behavior had a significant relationship (p <0.05) and have a coefficient correlation with positive value (r=0.535).Conclusion: The good mother’s commitment can make a good behavioral prevention of picky eating in toddlers. There needs to be more research on the factors that influence the behavioral prevention of picky eating. Keywords: Commitment, Mother, Picky Eating